Female seafarers adopt the high risk lifestyle of male seafarers. Issue 1 (January 1998) - Hansen, H L; Jensen, J
Abstract : OBJECTIVE: To study the mortality of women in an occupation known to have a high mortality among men. METHODS: A total of 6788 female seafarers of all job categories who had been employed on Danish merchant ships, passenger ships, and privately owned ferries between 1986 and 1993, were followed up until the end of 1993. RESULTS: Standardised mortality ratio (SMR) was 1.20 (95% confidence interval (95% CI) 0.89 to 1.58) for all causes of death and job categories together. For women in traditionally male jobs, SMR was 2.82 (1.41-5.05), whereas galley and catering staff had SMRs close to the general female population. The high mortality among women in traditional male jobs could be explained by a high risk of fatal accidents including occupational accidents. In the whole cohort, there were fewer deaths from natural causes than expected but an excess risk of death due to lung cancer, heart diseases, and non-natural deaths. CONCLUSION: The increased mortality could primarily be explained by an excess risk of fatal accidents and suicide. Especially, female seafarers entering traditional male jobs had a high risk of fatal accidents, not only at sea but also ashore. An excess risk of dying of lung cancer and heart diseases probably reflects a high tobacco consumption. Female seafarers are probably influenced by their occupation towards hazardous behaviour and a high risk lifestyle but people with a high risk lifestyle may also be attracted by or forced into high risk jobs such as traditional male jobs at sea.